2023
DOI: 10.3389/fcvm.2023.1230669
|View full text |Cite
|
Sign up to set email alerts
|

Serial echocardiographic evaluation of COVID-19 patients without prior history of structural heart disease: a 1-year follow-up CRACoV-HHS study

Agnieszka Olszanecka,
Wiktoria Wojciechowska,
Agnieszka Bednarek
et al.

Abstract: BackgroundIt is a well-known fact that COVID-19 affects the cardiovascular system by exacerbating heart failure in patients with preexisting conditions. However, there is a poor insight into the cardiovascular involvement and sequelae in patients without preexisting conditions. The aim of the study is to analyse the influence of COVID-19 on cardiac performance in patients without prior history of structural heart disease. The study is part of the CRACoV project, which includes a prospective design and a 12-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Given the limited data on CMR studies, one should also look into other imaging modalities. A current echocardiography study by Olszanecka et al reported FU data for 229 patients with mild to severe COVID-19 infection at 3, 6, and 12 months ( 26 ). They found a significant improvement in LV-SV as well as a reduction in LV mass accompanied by a lower systolic blood pressure at FU.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited data on CMR studies, one should also look into other imaging modalities. A current echocardiography study by Olszanecka et al reported FU data for 229 patients with mild to severe COVID-19 infection at 3, 6, and 12 months ( 26 ). They found a significant improvement in LV-SV as well as a reduction in LV mass accompanied by a lower systolic blood pressure at FU.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pulmonary edema is the main clinical manifestation, which can progress to cardiogenic shock or cardiac arrest and can lead to mortality in severe cases ( 7 ). COVID-19 exacerbates HF in patients with preexisting conditions by affecting the cardiovascular system ( 8 ). A significant association has been found between COVID-19 and ischemic HF (IHF), contributing to the progression of the disease and increasing mortality in patients with IHF ( 9 ).…”
Section: Introductionmentioning
confidence: 99%